The biological activity of bacterial starter fermented milk products - Матвєєва, О. Л.; Старинщак, В. В.; Решетняк, Л. Р. (Problems of Environmental Biotechnology, 2018)
In the article the changes in the quality of bacterial fermentation of ТМ «VIVO», «IPROVIT», «GOOD FOOD» are investigated depending on the frequency of reproduction of fermentation, optimal technological parameters for obtaining functional sour milk product, optimum temperature and time of fermentation are determined.